2022
DOI: 10.1136/jme-2022-108371
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of the algorithmic prediction of goal of care preferences: from theory to practice

Abstract: Artificial intelligence (AI) systems are quickly gaining ground in healthcare and clinical decision-making. However, it is still unclear in what way AI can or should support decision-making that is based on incapacitated patients’ values and goals of care, which often requires input from clinicians and loved ones. Although the use of algorithms to predict patients’ most likely preferred treatment has been discussed in the medical ethics literature, no example has been realised in clinical practice. This is due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 51 publications
0
35
0
5
Order By: Relevance
“…In their contribution ‘Ethics of the algorithmic prediction of goal of care preferences’1 Ferrario et al elaborate a from theory to practice contribution concerning the realisation of artificial intelligence (AI)-based patient preference prediction (PPP) systems. Such systems are intended to help find the treatment that the patient would have chosen in clinical situations—especially in the intensive care or emergency units—where the patient is no longer capable of making that decision herself.…”
Section: Introductionmentioning
confidence: 99%
“…In their contribution ‘Ethics of the algorithmic prediction of goal of care preferences’1 Ferrario et al elaborate a from theory to practice contribution concerning the realisation of artificial intelligence (AI)-based patient preference prediction (PPP) systems. Such systems are intended to help find the treatment that the patient would have chosen in clinical situations—especially in the intensive care or emergency units—where the patient is no longer capable of making that decision herself.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relative youth of those who experience aSAH and its typically sudden and unexpected onset, those directly affected tend to be unprepared and often lack written advance directives. Current studies have suggested the value of artificial intelligence to improve prognoses [ 16 ] and establish real-time decision-making support [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nietzche claimed that once we know why to live, we’ll suffer almost any how 1. Artificial intelligence (AI) is used widely for the how , but Ferrario et al now advocate using AI for the why 2. Here, I offer my doubts on practical grounds but foremost on ethical ones.…”
mentioning
confidence: 98%